Content Marketing Analysis in Increasing Customer Engagement and Purchase Decisions on Merchant Promotions at BNI Experience Website - Alfin Nurfadhilah Ramli; Dr. Osly Usman, M.Bus Syst; Meta Bara Berutu, S.E., M.M (Journal of Digital Business and Global Economy, 2025)
This study aims to analyze the influence of content marketing on customer engagement and purchase decisions regarding promo merchants featured on the BNI Experience website. The research employs a mixed-method approach using methodological triangulation to obtain a more comprehensive understanding of the studied phenomenon. Quantitative data were collected from 250 respondents selected through purposive sampling based on specific criteria, while qualitative data were obtained through in-depth interviews with two key informants from BNI who are directly involved in content strategy management. The quantitative analysis, using Structural Equation Modeling (SEM) with Partial Least Square (PLS), indicates that content marketing has a positive and significant effect on both customer engagement and purchase decisions. Furthermore, customer engagement is proven to be a significant mediating variable in the relationship between content marketing and purchase decisions. The qualitative analysis, through thematic interpretation, supports the quantitative findings by showing that content that is relevant, informative, easy to understand, easy to find, valuable, and consistent can build emotional engagement and drive customer purchase decisions. These findings suggest that an effective content marketing strategy not only strengthens customer relationships but also encourages conversion through more meaningful digital interactions. This research contributes to the development of digital marketing knowledge, particularly in the banking sector.